2021
DOI: 10.1111/tpj.15088
|View full text |Cite
|
Sign up to set email alerts
|

The emergence and evolution of intron‐poor and intronless genes in intron‐rich plant gene families

Abstract: Eukaryotic genes can be classified into intronless (no introns), intron-poor (three or fewer introns per gene) or intron-rich. Early eukaryotic genes were mostly intron-rich, and their alternative splicing into multiple transcripts, giving rise to different proteins, might have played pivotal roles in adaptation and evolution. Interestingly, extant plant genomes contain many gene families with one or sometimes few sub-families with genes that are intron-poor or intronless, and it remains unknown when and how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 62 publications
4
50
1
Order By: Relevance
“…The SRO genes in the same group showed similar numbers of exons and conserved structures in a variety of tomatoes, especially the SRO genes in group I, which had a highly consistent exon distribution and the largest number of motifs and were likely the core gene cluster in the tomato SRO family. However, compared with wild tomatoes, SRO genes in cultivated tomato often have longer gene structures and more introns than other genes in the same group, which means that SolySROs can achieve transcriptional diversification through alternative splicing and other processes, thus regulating more complex and extensive functions ( Liu et al, 2021 ). This was obviously not available in the SRO gene in wild tomatoes.…”
Section: Discussionmentioning
confidence: 99%
“…The SRO genes in the same group showed similar numbers of exons and conserved structures in a variety of tomatoes, especially the SRO genes in group I, which had a highly consistent exon distribution and the largest number of motifs and were likely the core gene cluster in the tomato SRO family. However, compared with wild tomatoes, SRO genes in cultivated tomato often have longer gene structures and more introns than other genes in the same group, which means that SolySROs can achieve transcriptional diversification through alternative splicing and other processes, thus regulating more complex and extensive functions ( Liu et al, 2021 ). This was obviously not available in the SRO gene in wild tomatoes.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds to the last two motifs in the analysis of upland cotton conserved motifs, which are contained in all GhEXO protein sequences. Moreover, it has been found that the structure of a gene permits its evolutionary analysis, and the pattern of exon/intron distribution is useful for its function ( Roy and Gilbert, 2006 ; Liu et al, 2021 ). In our study, exon/intron analysis indicated that most of the GhEXO genes have no introns, only 25% or fewer contain introns.…”
Section: Discussionmentioning
confidence: 99%
“…The 48 genes with reliable structures show consistent phylogenetic patterns (Figure S5). However, in all cases the CGTs could be described as intron‐less or intron poor (Liu et al ., 2021). In contrast, many of the putative TaUGTs , with low E value, are intron‐rich (Figure S6).…”
Section: Glucosyl Transferases In Wheatmentioning
confidence: 99%
“…Liu et al . (2021) speculate that loss of introns may be a factor in early land plant evolution allowing fast response to stress conditions and also may have facilitated faster developmental adaptations to life on land. Indeed, Vyroubalová et al .…”
Section: Glucosyl Transferases In Wheatmentioning
confidence: 99%
See 1 more Smart Citation